Six state molecular revolver mounted on a rigid platform. Issue 18 (25th April 2019) - Homberg, Jan; Lindner, Marcin; Gerhard, Lukas; Edelmann, Kevin; Frauhammer, Timo; Nahas, Yasmine; Valášek, Michal; Mayor, Marcel; Wulfhekel, Wulf
Abstract : The tip of an STM induces transitions between six rotational states in tripodal sulfur-anchored stands with rotational axes. Abstract : The rotation of entire molecules or large moieties happens at 100 ps time scales and the transition process itself is experimentally inaccessible to scanning probe techniques. However, the reversible switching of a molecule between more than two metastable states allows to assign a rotational switching direction. Rotational switching is a phenomenon that is particularly interesting with regard to possible applications in molecular motors. In this work, single tetraphenylmethane molecules deposited on a Au(111) surface were studied in a low temperature scanning tunneling microscope (STM). These molecules comprise rotational axes mounted on a tripodal sulfur-anchored stand and with the STM tip, we were able to induce transitions between six rotational states of the molecular motif. We were able to identify critical parameters for the onset of rotational switching and to characterize the influence of the local environment. The subtle difference between fcc and hcp stacking and the rotational state of neighboring molecules clearly influence the population of the rotational states.